(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Eight types of cereals viz., wheat grain, chopped wheat, paddy grain, rice grain, maize grain, chopped maize, rice bran, mixture of rice bran and chopped rice were fed to observe the development parameters like egg, larva, pupa and adult stages of Corcyra cephalonica (stainton) for three consecutive generations. The parasitism efficiency of Trichogramma chilonis (Ishii) was also evaluated on the resultant host eggs of C. cephalonica. The C. cephalonica revealed the highest number of eggs (115.6 female1), higher hatchability (92.9%), extented larval duration (45.9 days), increased larval weight (0.058 gm), survival rate (88.3%), adult emergence rate (93.5%), and male and female longevity (7.7, 7.2 days respectively) when they were reared on chopped wheat. On the other hand, the lowest number of egg was found on paddy husk (29.2 female-1). The lowest hatchability (45.6%), larval duration (45.9 days), larval weight (0.029gm), and survival rate (38.2%), pupal duration (17.9 days) adult emergence (42.0%), male and female longevity (4.8 and 4.7 days respectively) were found on paddy husk. The effect of food materials also reflected on the parasitism efficiency of the egg parasitoid T. chilonis. The highest percent egg parasitization was done by the T. chilonis on the host eggs, reared on chopped wheat (94.8±0.07%) followed by wheat grain (82.5±0.08%) and chopped maize (73.8±0.09%). On the other hand, the lowest parasitism was obtained when the larvae were reared on paddy husk (42.2±0.14 %) and paddy grain (48.8±0.05 %). Bangladesh J. Agril. Res. 41(1): 183-194, March 2016